Road accident database management system / Fadzilah Mahmmod - Mahmmod, Fadzilah (1991)
This thesis is to develop a software of Road Accident Database Management System (RADMS) for data input and analysis of road accident. The format of the system was based on road accident data form used by the Royal Police Department of Malaysia, form POL 27. This thesis covers only on computer programming using dBase III plus language and operated on personal computer of IBM compactable or equivalent. The system developed can be used for road accident data base inventory and also perform basic statistical analysis to reveal the trends and patterns of road accidents over a specified period time. By knowing these facts and identification of black spot , essential preventive counter-measures and precautions can be considered for implementation and for future planning. However, it is worth to mention that the statistical information obtained from the system should be interpreted intelligently.